2006
DOI: 10.1007/s00203-006-0117-5
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, and gene cloning of 4-hydroxybenzoate decarboxylase of Enterobacter cloacae P240

Abstract: We found the occurrence of 4-hydroxybenzoate decarboxylase in Enterobacter cloacae P240, isolated from soils under anaerobic conditions, and purified the enzyme to homogeneity. The purified enzyme was a homohexamer of identical 60 kDa subunits. The purified decarboxylase catalyzed the nonoxidative decarboxylation of 4-hydroxybenzoate without requiring any cofactors. Its Km value for 4-hydroxybenzoate was 596 microM. The enzyme also catalyzed decarboxylation of 3,4-dihydroxybenzoate, for which the Km value was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…The enzymic transformation of 2H1NA to 2-naphthol is attributed to the action of a non-oxidative decarboxylase. Similar enzyme activity was noted for the decarboxylation of other aromatic acids (Gu et al, 2011;Matsui et al, 2006;Yoshida et al, 2004). Formation of 1-naphthol from 1H2NA has previously been documented in the metabolism of phenanthrene (Feng et al, 2012, and references therein), but this is the first report on the bacterial metabolism of 2H1NA via 2-naphthol.…”
Section: Discussionsupporting
confidence: 77%
“…The enzymic transformation of 2H1NA to 2-naphthol is attributed to the action of a non-oxidative decarboxylase. Similar enzyme activity was noted for the decarboxylation of other aromatic acids (Gu et al, 2011;Matsui et al, 2006;Yoshida et al, 2004). Formation of 1-naphthol from 1H2NA has previously been documented in the metabolism of phenanthrene (Feng et al, 2012, and references therein), but this is the first report on the bacterial metabolism of 2H1NA via 2-naphthol.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, in P. agglomerans, SDS-PAGE analysis indicated that the purified gallate decarboxylase was homogeneous and consisted of six identical subunits of 57 kDa in molecular mass (6). In addition, purified 4-hydroxybenzoate decarboxylase from E. cloacae was a homohexamer of identical 60-kDa subunits (33). The molecular masses of these proteins are in accordance with the masses of their respective C subunits deduced from in silico sequence analysis.…”
Section: Discussionsupporting
confidence: 66%
“…Over half (49) of these 76 genes were associated with virulence and included those found on the LEE, as well as other non-LEE-encoded T3SS effectors. Of note, among the remaining shared genes was a cluster with a putative role in the production of 4-hydroxybenzoate decarboxylase, which is found sporadically in other members of the Enterobacteriaceae, as well as elsewhere, and may be involved in metabolism of aromatic compounds under anaerobic conditions (20,53,56).…”
Section: Resultsmentioning
confidence: 99%